PENGARUH SUNSET POLICY, TAX AMNESTY DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK (Studi Pada Wajib Pajak Orang Pribadi di KP2KP Masohi) - Elna Marsye Pattinaja; Revi Wilhelmina Silooy (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2018)
Sunset policy is the elimination of administrative sanctions taxation inthe form of interest. State revenue from the tax sector increased from the program.This indicates that the implementation of sunset policy raises the awareness of thetaxpayer to fulfill his tax obligations. The purpose of this study is to examinewhether sunset policy, tax amnesty and awareness of taxpayers affect thecompliance of individual taxpayers on KP2KP Masohi.Population in this research is all individual taxpayer recorded in KP2KPmasohi with amount 2,136 taxpayer. The sample in this study are taxpayers ofindividuals (employees, civil servants, military, police or other) who have a fixedincome. . Sampling technique in this research is by purposive sampling that issampling technique based on certain criterion.The result of this research is Sunset policy has a significant effect ontaxpayer compliance on KP2KP Masohi, Amnesty tax has a significant effect ontaxpayer compliance on KP2KP Masohi, taxpayer awareness has significanteffect on personal taxpayer compliance at KKP Pratama Ambon.